2003
DOI: 10.1128/mcb.23.7.2577-2586.2003
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hypermethylation in Drosophila melanogaster Causes Irregular Chromosome Condensation and Dysregulation of Epigenetic Histone Modifications

Abstract: The level of genomic DNA methylation plays an important role in development and disease. In order to establish an experimental system for the functional analysis of genome-wide hypermethylation, we overexpressed the mouse de novo methyltransferase Dnmt3a in Drosophila melanogaster. These flies showed severe developmental defects that could be linked to reduced rates of cell cycle progression and irregular chromosome condensation. In addition, hypermethylated chromosomes revealed elevated rates of histone H3-K9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 67 publications
7
23
0
Order By: Relevance
“…Consistent with results from other organisms (Jackson et al, 2002;Tamaru and Selker, 2001) this revealed an unambiguous reduction in DNA methylation (Fig. 1F) and confirmed that DNA methylation in Drosophila interacts with histone H3-K9 methylation (Weissmann et al, 2003). Finally, we also incubated wild-type embryos with the (cytosine-5) DNA methyltransferase inhibitor 5-azacytidine.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with results from other organisms (Jackson et al, 2002;Tamaru and Selker, 2001) this revealed an unambiguous reduction in DNA methylation (Fig. 1F) and confirmed that DNA methylation in Drosophila interacts with histone H3-K9 methylation (Weissmann et al, 2003). Finally, we also incubated wild-type embryos with the (cytosine-5) DNA methyltransferase inhibitor 5-azacytidine.…”
Section: Resultssupporting
confidence: 72%
“…Studies in Neurospora and Arabidopsis have shown that mutations in Su(var)3-9 histone H3-K9 methyltransferase homologues result in reduced levels of DNA methylation (Jackson et al, 2002;Tamaru and Selker, 2001). In addition, we have shown recently that DNA hypermethylation phenotypes in Drosophila can be rescued by mutations in the Su(var)3-9 gene (Weissmann et al, 2003), which suggested a preservation of this phenomenon in flies. The Drosophila Su(var)3-9 gene has been shown to encode a major histone H3-K9 methyltransferase activity in fly embryos (Schotta et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of indirect evidence support this proposal. First, excessive DNA methylation, produced by expression of a mouse DNA methylase in Drosophila, produces general heterochromatin-like phenotypes that are relieved by a suppressor-of-variegation mutation (Weissmann et al 2003). This suggests that DNA methylation might play an important role in the formation of heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53] Although the exact molecular events involved remain to be determined, it is believed that the link between genomic methylation and heterochromatin stability is correlated with Suv39 HMTase. 60 This connection is attractive given the recent study by Selker and co-workers that trimethH3K9 is a mark for DNA methylation and provides a functional link between these epigenetic pathways. 61 Although covalent histone modifications are crucial for regulating genomic methylation patterns in Neurospora, there seem to be exceptional differences in plants and mammals; for example, DNA methylation is dispensable in Neurospora.…”
Section: The Two Sides Of Genomic Methylationmentioning
confidence: 99%